Ebstein's anomaly in persistent common atrioventricualr canal. - Caruso, G (1978)
This report documents 2 patients who presented with cyanosis early in life. In both instances the necropsy showed the simultaneous occurrence of an imcomplete type of persistent atrioventricular canal and an Ebstein's malformation of the "tricuspid" valve component. In the first patient no clinical investigations were done. In the second patient the electrocardiogram was consistent with persistent atrioventricular canal and the angiocardiogram showed the characteristic goose-neck deformity. Moreover, an abnormality of the right cardiac contour was seen, which in retrospect was correlated with the right-sided Ebstein's malformation. Ebstein's anomaly may significantly alter the clinical and haemodynamic profile of atrioventricular canal and should be considered in atypical cases. The presence of Ebstein's anomaly will complicate surgical repair of the atrioventricular canal.